2021
DOI: 10.3389/fimmu.2021.742449
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota–Gut–Brain Axis and Epilepsy: A Review on Mechanisms and Potential Therapeutics

Abstract: The gut–brain axis refers to the bidirectional communication between the gut and brain, and regulates intestinal homeostasis and the central nervous system via neural networks and neuroendocrine, immune, and inflammatory pathways. The development of sequencing technology has evidenced the key regulatory role of the gut microbiota in several neurological disorders, including Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis. Epilepsy is a complex disease with multiple risk factors that affect mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 191 publications
0
53
1
Order By: Relevance
“…MGBA is a bidirectional communication system between the enteric microbiota and the brain, which mainly consists of the central nervous system (CNS), enteric nervous system (ENS), and gastrointestinal microbiota (GIM) ( 7 , 8 ). Communication is exerted through many pathways, namely, neural tracts, immunological, inflammatory, and neuroendocrine pathways ( 9 ). In the last decade, scientific evidence has increased substantially, highlighting the relation between GIM and neuropsychiatric and neurological disorders, namely, epilepsy ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MGBA is a bidirectional communication system between the enteric microbiota and the brain, which mainly consists of the central nervous system (CNS), enteric nervous system (ENS), and gastrointestinal microbiota (GIM) ( 7 , 8 ). Communication is exerted through many pathways, namely, neural tracts, immunological, inflammatory, and neuroendocrine pathways ( 9 ). In the last decade, scientific evidence has increased substantially, highlighting the relation between GIM and neuropsychiatric and neurological disorders, namely, epilepsy ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…SCFAs are fatty acids with fewer than six carbons produced by bacteria, such as Bifidobacterium, Clostridium, and Lactobacillus during polysaccharide fermentation in the colon ( 19 , 20 ). The main SCFAs produced by GIM are acetate, propionate, and butyrate, which are absorbed through the intestine before being circulated to the liver and other organs, namely, the brain ( 9 , 20 ). SCFAs play a major role in maintaining a healthy intestine as they are the main energy source of enterocytes and promote intestinal barrier integrity ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the relationship between the brain‐gut axis and epilepsy is still at the preliminary stage. Recent studies on murine models have shown a close relation between gut microbiota and the occurrence of multiple types of epilepsy 88 . However, most of the underlying mechanisms are still unknown.…”
Section: Overview Of In Vivo and In Vitro Epilepsy Models Taking Into...mentioning
confidence: 99%
“…Recent studies on murine models have shown a close relation between gut microbiota and the occurrence of multiple types of epilepsy. 88 However, most of the underlying mechanisms are still unknown. Progress is being made in developing strategies to investigate the bidirectional communication between the gut and the brain in general with animal models, like germ-free mice, being essential for deepening our understanding of how microbiota alterations shape brain pathophysiology.…”
Section: In Vitro Mgb Axis and Epilepsy Modeling: Challenges For A Te...mentioning
confidence: 99%
“…There might be other processes influencing to lesser extent the onset and progression of epileptogenesis, which might be targeted by brain stimulation. Recently, considerable insight has been gained into the role gastrointestinal microbiota plays in epilepsy ( 181 ). Even though short VNS did not alter gut microbiota composition in mice ( 182 ), repeated TMS of prefrontal cortex influenced rectal function of human volunteers, supposedly also affecting their microbiota ( 183 ).…”
Section: Future Perspectivesmentioning
confidence: 99%